Capture system for human motion imitation by a fixed base planar robot (2014)
This paper shows the implementation of a motion capture system of low cost, using Kinect for imitation of movement in the frontal plane with a fixed base planar robot. The inverse kinematics for mapping human motion through Cartesian coordinates (x, y, z) provided by sensor and turn them into joint coordinates (q1 , q2 , ..., q9 ), which are the angular positions of reference for the robot. These reference trajectories were used to imitate human movement by a planar robot with nine degrees of freedom.